ASPEK SOSIAL DALAM NOVEL SANG PEMIMPI KARYA ANDREA HIRATA: TINJAUAN SOSIOLOGI SASTRA - Boimin Boimin; Sri Wahyuningtyas (Universitas Sarjanawiyata Tamansiswa, 2015)
This study aimed to describe these things. (1) Figures and characterizations in Sang Pemimpi Novel. (2) The flow of Sang Pemimpi Novel. (3) Structure of Sang Pemimpi Novel. (4) Environmental issues in Sang Pemimpi Novel. 5) The problem of poverty Sang Pemimpi Novel. (6) The issue of social inequality in Sang Pemimpi Novel. This study is a qualitative descriptive study. Data used in the form paragraphs which contain units of events regarding the social aspects related to social issues. Sources of data in the form of Sang Pemimpi Novel. The instrument of this study is the researchers themselves armed with a set of science concepts related to the problem under study. The data collection technique using the technique to read and record the techniques. Data analysis technique used is descriptive qualitative focus on character and characterization, plot, setting, and social aspects related to social issues that include environmental concerns, problems of poverty and social imbalances in Sang Pemimpi Novel by Andrea Hirata. The results of this study as follows. (1) Figures and characterizations. The main character is a character that has the curls of hard work, religious, and ambitious. Additional characters are a) Arai who had unyielding and steadfast character, b) Jimbron who has a good-natured and reserved character, c) Mr. Balia who has a smart and thoughtful character, d) Mr. Mustar who has the character of discipline and care. (2) The flow of Sang Pemimpi Novelis the flow of the mixture. (3) Structure of Sang Pemimpi Novelis follows: (a) setting the place on Belitong island which include; Magai cities and buildings Theaters and in Bogor which include; Bogor terminal, copy center, post office, (b) setting a time around the 1980s and 1990s, (c) social background that lower class people's lives. (4) Environmental issues in Sang Pemimpi Novelis the exploitation PN Timah which cause environmental damage. (5) The problem of poverty in Sang Pemimpi Novel is when figures curls, Arai and Jimbron who could not sustain daily life. The problem of poverty is also experienced by prominent Mahander, Mak Cik Maryamah, Bang Zaitun and Laksmi. (6) The issue of social inequality in the novel The Dreamer is an imbalance in the lives of indigenous peoples of Belitong with the elite in the PN Timah.